2021
DOI: 10.3389/fncel.2020.627887
|View full text |Cite
|
Sign up to set email alerts
|

Megalencephalic Leukoencephalopathy: Insights Into Pathophysiology and Perspectives for Therapy

Abstract: Megalencephalic leukoencephalopathy with subcortical cysts (MLC) is a rare genetic disorder belonging to the group of vacuolating leukodystrophies. It is characterized by megalencephaly, loss of motor functions, epilepsy, and mild mental decline. In brain biopsies of MLC patients, vacuoles were observed in myelin and in astrocytes surrounding blood vessels. It is mainly caused by recessive mutations in MLC1 and HEPACAM (also called GLIALCAM) genes. These disease variants are called MLC1 and MLC2A with both typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 71 publications
(160 reference statements)
0
21
0
Order By: Relevance
“…They might also regulate the trafficking and biosynthetic processing of these partners ( 66 ). Considering MLC1, although the sequence homology to tetraspanins is very low (~20%), it passes the membrane eight times, but biochemical studies indicate that each four transmembrane domains can be considered as a duplicate ( 6 ). As tetraspanins, MLC1 also oligomerizes with himself and forms a tight complex with GlialCAM, a single-pass transmembrane domain of the Ig family ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They might also regulate the trafficking and biosynthetic processing of these partners ( 66 ). Considering MLC1, although the sequence homology to tetraspanins is very low (~20%), it passes the membrane eight times, but biochemical studies indicate that each four transmembrane domains can be considered as a duplicate ( 6 ). As tetraspanins, MLC1 also oligomerizes with himself and forms a tight complex with GlialCAM, a single-pass transmembrane domain of the Ig family ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…These genes encode for membrane proteins that form a complex located at cell–cell junctions in brain perivascular astrocytic processes or in Bergmann glia at the cerebellum ( 5 ). A reduced number of patients (2%) do not harbor mutations in MLC1 or GLIALCAM , suggesting the existence of other unknown disease genes ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cycloheximide (CHX) treatment to assess MLC1 degradation kinetics, was carried out by stimulating cells with CHX (100 µg/mL, Sigma-Aldrich, Darmstadt, Germany) for different time lengths (1,3,4 or 5 hours, h). After all stimulations, cells were washed in phosphate buffered saline (PBS), collected by scraping and centrifuged at 2700g at 4°C for 10 min.…”
Section: Cell Cultures and Treatmentsmentioning
confidence: 99%
“…MLC1 is a 377-amino acid membrane protein with eight predicted transmembrane domains and short cytoplasmic amino and carboxylic tails that shows very low similarity with some ion channels (reviewed in [1]). MLC1 is almost exclusively expressed in the brain where it localizes preferentially at astrocyte end-feet contacting blood vessels and meninges, and in the Bergmann glia of the cerebellum [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The pathological outcome of MLC disease is impaired motor coordination, cognitive function and epilepsy. The genetic aetiology indicates that approximately 75% of affected patients carry genetic mutations in the MLC1 gene [1][2][3][4][5][6][7][8][9][10]. Previous studies have suggested that MLC1 is crucial for astroglial interactions and water homeostasis, which might cause the pathological outcomes of MLC disease [11][12][13].…”
Section: Introductionmentioning
confidence: 99%